Uji efektivitas salep kombinasis Nothopnax sculleturium (daun mangkokan) dan Colocasia esculenta L. (daun talas) terhadap penyembuhan luka sayat kelinci jantan - Ekawaty Suryani Mastari; Hanafis Sastra Winata; Ruth Mayana Rumanti; Sari Bulan Novita (Fakultas Farmasi Universitas Tjut Nyak Dhien, 2026)
Background: Nothopanax scutellarium (mangkokan leaves) and Colocasia esculenta L. (taro petioles) contain bioactive compounds such as flavonoids, saponins, tannins, terpenoids, and steroids, which play essential roles in wound healing. Objective: This study aimed to evaluate the effectiveness of a topical ointment containing a combination of ethanolic extracts of mangkokan leaves and taro petioles on incised wound healing in male rabbits. Methods: A laboratory experimental study with a post-test-only control group design was conducted using three ointment formulas (10%:5%, 7.5%:7.5%, and 5%:10%), alongside positive (povidone-iodine) and negative controls. Wound length was measured daily for 10 days. Data were analysed using one-way ANOVA followed by Tukey's post-hoc test at a significance level of α = 0.05. Results: All formulations significantly accelerated wound healing compared with the negative control (p < 0.05). The 5%:10% formulation achieved complete wound closure on day 7, showing a statistically significant difference from the positive control (p < 0.05). Conclusion: The combination of mangkokan leaf and taro petiole extracts effectively promotes incised wound healing, with the 5%:10% formula demonstrating the most optimal effect. These findings support the potential of developing this herbal ointment as a safe and efficient antiseptic alternative.